Analisis Kelayakan dan Strategi Bisnis Berkelanjutan Agribisnis Hanjeli: Studi Kasus Koperasi Pantastik, Sumedang - Tania, Fransisca Johana; Tridakusumah, Ahmad Choibar; Ernah, Ernah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Hanjeli (Coix lacryma-jobi L.) is a local cereal crop with strong potential as an alternative food source and economic commodity rooted in local wisdom. However, the development of hanjeli agribusiness still faces several challenges, such as limited resources, suboptimal marketing strategies, and low public awareness. This study aims to evaluate the economic feasibility and formulate sustainable business strategies for hanjeli agribusiness at the Pantastik Cooperative in Wado, Sumedang. A case study approach was employed, combining a qualitative method using the Sustainable Business Model Canvas (SBMC) framework and a quantitative approach through farm feasibility analysis. The results indicate that the hanjeli business model demonstrates strengths in its value proposition, particularly in delivering eco-social benefits such as farmer empowerment, biodiversity conservation, and environmental preservation. Nevertheless, the model also encounters critical barriers in distribution channels, limited access to capital, and human resource capacity. The feasibility analysis reveals that hanjeli farming is economically viable, with an R/C ratio of 2.4 indicating profitability, and a break-even point (BEP) of 128 kg per production cycle. This study highlights significant opportunities to advance sustainable hanjeli agribusiness through the strategic integration of economic, social, and environmental dimensions. The findings imply the need for collaborative efforts among government stakeholders, cooperatives, the private sector, and communities to strengthen the resilience and sustainability of inclusive local agribusiness systems.